Understanding phenomenology - "Cerbone, David R" (Chesham, 2006)
This book approaches the topic of intercultural understanding in philosophy from a phenomenological perspective. It provides a bridge between Western and Eastern philosophy through in-depth discussion of concepts and doctrines of phenomenology and ancient and contemporary Chinese philosophy. Phenomenological readings of Daoist and Buddhist philosophies are provided: the reader will find a study of theoretical and methodological issues and innovative readings of traditional Chinese and Indian philosophies from the phenomenological perspective. The author uses a descriptive rigor to avoid cultural prejudices and provides a non-Eurocentric conception and practice of philosophy. Through this East-West comparative study, a compelling criticism of a Eurocentric conception of philosophy emerges. New concepts and methods in intercultural philosophy are proposed through these chapters. Researchers, teachers, post-graduates and students of philosophy will all find this work intriguing, and those with an interest in non-Western philosophy or phenomenology will find it particularly engaging.
Keywords: Phenomenology